KINERJA KEUANGAN PT. KERSA GUNUNG WASADA - -, Beti Darnawati (EKONOMIA, 2014)
The development of an enterprise can be seen from the financial statements, from year to year or from one period to the next period. Financial Budget and Cost Advantages reflected in the financial statements, financial statements in which it is a picture of a company's ability liabilities (long term and short term) to be met. But PT Kersa Gunung Wasada not know how much strength and weaknesses as well as the possibility of expanding its business when viewed in terms financialnya because the company has not been analyzed keuanganya reports using appropriate financial ratios. Based on this background, the problems in this thesis is "Is Profitability Ratio analysis at PT Kersa Gunung Wasada in 2012 increased compared to 2011            The purpose of this paper is to know To know and analyze the ratio set by the company in optimizing the acquisition keutungan.From the analysis and discussion, it can be concluded as follows: Judging from the ratio of profitability at the net profit margin ratio does not increase or decrease (stable) ie 2% this is due to sales and operational costs have increased. Payback ratio increased only 1%, this is due to an increase in total assets. Based on the conclusions that have been put forward the hypothesis which states that the ratio of stable profitability in 2012, an increase compared to 2011, accepted